Rapid Antibiotic Susceptibility Testing of Tier-1 Agents Bacillus anthracis, Yersinia pestis, and Francisella tularensis Directly From Whole Blood Samples - Rotem, Shahar; Shifman, Ohad; Aftalion, Moshe; Gur, David; Aminov, Tamar; Aloni-Grinstein, Ronit (Frontiers in Microbiology, 2021)
Rapid antibiotic susceptibility tests, performed directly on whole blood samples, will offer great clinical advantages. This issue is of considerable importance when it comes to bio-terror pathogens where prompt antibiotic treatment should be offered to infected patients as well as prophylaxis to suspected exposed individuals. Herein we describe a novel and rapid method, named MAPt that is based on the direct application of a blood sample onto solid agar that has been embedded with different concentrations of the tested antibiotic. Following a short incubation, bacterial growth is monitored by qPCR. The method was applied on blood cultures and whole blood samples spiked with the bio-terror pathogens Bacillus anthracis, Yersinia pestis and Francisella tularensis. The use of agar medium, which better supports the growth of bacteria at low concentrations, together with the use of qPCR, which provides sensitivity and specificity, allowed minimal inhibitory concentration (MIC) determination to a wide range of bacterial concentrations, ranging from ~5x102 cfu/ml up to 108 cfu/ml. The omission of the enrichment procedure in blood culture and the isolation step, both required in standard ASTs, allowed a dramatic reduction in time-to-answer, from a few days to a few hours. The total time required for MIC determination was ~6 h for fast-growing bacteria, such as B. anthracis, and 12 -16 h for slow-growing bacteria, represented by Y. pestis and F. tularensis. Accordingly, MAPt may offer health authorities means for public preparedness in the case of a bio-terror attack as well as prompt clinical treatment options in common blood stream infections.